A Study on the Effect of Ethrel on Uniformity of Peach Ripening - AHMED, HUSAIN S.; SHALADAN, MOHAMED S. (The Libyan Journal of Agriculture, 2023)
Twelve, four year-old ‘Coronado’ peach trees were sprayed with 0, 100, 250, and 500 ppm ethrel, one month before harvest. Ethrel at all concentrations, had significantly increased the uniformity of fruits ripening, and produced softer fruits. Treatment with Ethrel had no effect on % dry weight, % total soluble solids, fruit length, fruit diameter, and length/diameter. Serious defoliation, fruit abscission, and gum exudation were observed.